Evelines: similarities and Differences between James Joyce’s Literature and Sara Benvenuto’s Film Adaptation in the Sociocultural Context - Damasceno, Isabela David de Lima; Ribeiro, Raquel Ferreira; Benvenuto, Sara Mabel Ancelmo (TradTerm, 2023)
This article proposes a comparison between the short story character “Eveline”, by James Joyce, which takes place in Ireland at the beginning of the 20th century, and Eveline, the short film Válvula main character, directed by Sara Benvenuto (2020). This one takes place in our times, in Iguatu, a city in the backlands of Ceará state. Both characters include the possibilities of changing their lives, but they also deal with retraints imposed by their sex and their sociocultural context. Supporting the discussion, it is considered Hutcheon’s (2013) adaptation concept (2013), Lefevere's notion of rewriting (1992) and the study of cinematographic aesthetics by Gardies et al. (2007). We carried the analysis through three perspectives: a literary analysis, a construction process of the adaptation from the film production, and from a pedagogical perspective. We conclude that although there are clear similarities between both narratives, the cultural contexts of the 1900s Dubliner woman and the 2020 rural woman from Iguatu stand out.